2017
DOI: 10.1038/nature24297
|View full text |Cite
|
Sign up to set email alerts
|

Drug-tolerant persister cancer cells are vulnerable to GPX4 inhibition

Abstract: Acquired drug resistance prevents cancer therapies from achieving stable and complete responses.1 Emerging evidence implicates a key role for nonmutational drug resistance mechanisms underlying the survival of residual cancer “persister” cells.2-4 The persister cell pool constitutes a reservoir from which drug-resistant tumours may emerge. Targeting persister cells therefore presents a therapeutic opportunity to impede tumour relapse.5 In an earlier report, we found that cancer cells in a high mesenchymal ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
1,043
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,226 publications
(1,082 citation statements)
references
References 23 publications
33
1,043
3
3
Order By: Relevance
“…It was recently demonstrated that a mesenchymal or persister cell state is highly dependent on GPX4 peroxidase activity for survival, highlighting the potential for co-treatment with GPX4 inhibitors to overcome epithelial-mesenchymal transition (EMT)-related resistance mechanisms (Hangauer et al, 2017; Viswanathan et al, 2017). These results are in line with our findings as low MITF melanoma cells do exhibit mesenchymal-like expression patterns and phenotype (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that a mesenchymal or persister cell state is highly dependent on GPX4 peroxidase activity for survival, highlighting the potential for co-treatment with GPX4 inhibitors to overcome epithelial-mesenchymal transition (EMT)-related resistance mechanisms (Hangauer et al, 2017; Viswanathan et al, 2017). These results are in line with our findings as low MITF melanoma cells do exhibit mesenchymal-like expression patterns and phenotype (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, metastasizing cells could be more sensitive to ferroptosis, and treatment with ferroptosis inducing drugs may potentially limit metastasis. Characterization of the in vivo efficacy of ferroptosis inducing compounds is currently limited by lack of compounds with sufficient bioavailability (Viswanathan et al, 2017; Hangauer et al, 2017). However, genetic experiments using GPX4 knockout melanoma cells have demonstrated that increased ferroptosis sensitivity observed in vitro can be recapitulated in vivo either alone or in combination with BRAF inhibition (Viswanathan et al, 2017; Hangauer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As observed in cancer progression, this transition has been linked to chemoresistance phenotypes; heterogeneity in epithelial versus mesenchymal state as measured by fluorescent lineage markers correlates with resistance to lethal drug treatments in lung and pancreatic cancer (Fischer et al 2015; Zheng et al 2015). Cells in a mesenchymal state that are less sensitive to chemotherapeutics may display other targetable sensitivities, such as a reliance on the lipid peroxide detoxifying enzyme glutathione peroxidase 4 (GPX4); this dependency can be exploited by inducing ferroptosis, an oxidative, non-apoptotic cell death pathway, in mesenchymal cells (Hangauer et al 2017; Viswanathan et al 2017). …”
Section: Cellular Manifestations Of Molecular Heterogeneity Impactingmentioning
confidence: 99%
“…This combinatorial approach provides a model for the potential therapeutic application of new insights into non-genetic heterogeneity among cancer cells. Analysis of DTPs generated from multiple combinations of cancer cell lines and drugs, for example, showed a common dependence on GPX4 in these subpopulations (Hangauer et al 2017). This is consistent with work discussed above showing a correlation between a mesenchymal gene signature, therapy resistance, and dependence on GPX4 (Viswanathan et al 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…This therapeutic approach is made plausible by the recent advances in targeted antioxidants that scavenge ROS at specific sites such as mitochondrial complex I or III (97,98). Furthermore, identification of cancer cell dependencies on specific antioxidants such as GPX4 encourages the development of molecules that disable such antioxidant proteins to potentiate the distant damaging ROS (66,99). Importantly, the dosage of the anti-and/or pro-oxidants must be regulated to preserve the redox signaling necessary for the healthy cells including anti-tumor T cells.…”
Section: Looking Forwardmentioning
confidence: 99%